Synthetic Strategy for Aryl(alkynyl)phosphinates by a Three-Component Coupling Reaction Involving Arynes, Phosphites, and Alkynes - Ji, Su Hyun; Kim Soomin; NAM, GHIL SOO; Lee, Duck-Hyung; Han, Seojung (American Chemical Society, 2022)
An efficient and straightforward method for the synthesis of aryl(alkynyl)phosphinates was developed via a three-component coupling reaction involving arynes, phosphites, and alkynes. An array of aryl(alkynyl)phosphinates were produced from both aryl and aliphatic group-substituted acetylenes. This opera-tionally simple reaction is tolerant to many functional groups, affording various aryl(alkynyl)phosphinates in moderate to good yields. The synthetic utility of alkynyl phosphinates afforded by this method was demonstrated by the elaboration of the products into various phosphorus-containing compounds.